2018
DOI: 10.3389/fonc.2018.00551
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Courses of Radiosurgery for New Brain Metastases to Defer Whole Brain Radiotherapy: Feasibility and Outcome With Validation of the New Prognostic Metric Brain Metastasis Velocity

Abstract: Purpose: Stereotactic radiosurgery (SRS) is the preferred primary treatment option for patients with a limited number of asymptomatic brain metastases. In case of relapse after initial SRS the optimal salvage treatment is not well defined. Within this retrospective analysis, we investigated the feasibility of repeated courses of SRS to defer Whole-Brain Radiation Therapy (WBRT) and aimed to derive prognostic factors for patient selection.Materials and Methods: From 2014 until 2017, 42 patients with 197 brain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…Ogawa et al [ 7 ] analyzed 31 patients with in-field local tumor relapses of NSCLC or lung metastasis and reported that repeat stereotactic body radiotherapy (SBRT) constitutes a viable therapeutic regimen. Further Fritz et al [ 8 ] assessed the feasibility of repeat stereotactic radiosurgery (SRS) in 42 patients harboring 197 brain metastases with 16 patients having undergone minimum three courses of SRS. The authors concluded that repeat SRS constitutes a reasonable treatment option in selected patients to delay rescue whole-brain radiation therapy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogawa et al [ 7 ] analyzed 31 patients with in-field local tumor relapses of NSCLC or lung metastasis and reported that repeat stereotactic body radiotherapy (SBRT) constitutes a viable therapeutic regimen. Further Fritz et al [ 8 ] assessed the feasibility of repeat stereotactic radiosurgery (SRS) in 42 patients harboring 197 brain metastases with 16 patients having undergone minimum three courses of SRS. The authors concluded that repeat SRS constitutes a reasonable treatment option in selected patients to delay rescue whole-brain radiation therapy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further Fritz et al [ 8 ] assessed the feasibility of repeat stereotactic radiosurgery (SRS) in 42 patients harboring 197 brain metastases with 16 patients having undergone minimum three courses of SRS. The authors concluded that repeat SRS constitutes a reasonable treatment option in selected patients to delay rescue whole-brain radiation therapy [ 8 ]. Barton et al [ 9 ] conducted an epidemiological calculus in more than 60,000 patients to assess the retreatment rate in different radio-oncological facilities, and found that it was fairly similar.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of BMV has since been validated in several other international patient populations. 58 , 59 …”
Section: Radiotherapymentioning
confidence: 99%
“…From common primary cancer sites such as lung, breast, and melanoma, brain metastasis occurs in 15% to 40% of the cancer patients 2,3 . The treatment of metastatic brain tumors depends on the number of metastatic tumors, extracranial tumor status, and performance status 4–6 . Currently, whole‐brain radiation therapy (WBRT) is considered a well‐established treatment for patients with multiple brain metastases.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The treatment of metastatic brain tumors depends on the number of metastatic tumors, extracranial tumor status, and performance status. [4][5][6] Currently, whole-brain radiation therapy (WBRT) is considered a well-established treatment for patients with multiple brain metastases.…”
mentioning
confidence: 99%